STRATEGI PEMASARAN MEDIA SOSIAL DALAM MENINGKATKAN KETERLIBATAN DAN LOYALITAS GENERASI Z - Maslahatun Maslahatun; Milka Pricilia; Rizka Aulia; Zaskia Ananta Lola Ruga (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Social media marketing is a process that encourages individuals to promote their websites, products, or services through online social channels and to communicate by tapping into a much larger community that has greater possibilities for marketing than through traditional advertising channels. This research uses a descriptive qualitative approach to analyze social media marketing strategies that are effective in increasing the engagement and loyalty of Generation Z. This research shows that the impact of social media marketing on consumer loyalty, especially in the TikTok Shop, is quite large, as well as building brand image in Generation Z. . Creative and interactive social media marketing, such as creating unique short video content and collaborating with influencers, can increase engagement and foster emotional bonds with customers. Generation Z values ​​authenticity and social value, so they are more loyal to brands that provide authentic material that is relevant to their lifestyle. Data-driven methods for understanding audience preferences, consistent communications, and promotions that leverage analytical technology and current trends are critical to marketing success. With innovative and open strategies, companies can develop a good brand image, strengthen emotional ties, and encourage long-term loyalty among the Millennial Generation.